7=x(-13+x)-11+6x

Simple and best practice solution for 7=x(-13+x)-11+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7=x(-13+x)-11+6x equation:


Simplifying
7 = x(-13 + x) + -11 + 6x
7 = (-13 * x + x * x) + -11 + 6x
7 = (-13x + x2) + -11 + 6x

Reorder the terms:
7 = -11 + -13x + 6x + x2

Combine like terms: -13x + 6x = -7x
7 = -11 + -7x + x2

Solving
7 = -11 + -7x + x2

Solving for variable 'x'.

Combine like terms: 7 + 11 = 18
18 + 7x + -1x2 = -11 + -7x + x2 + 11 + 7x + -1x2

Reorder the terms:
18 + 7x + -1x2 = -11 + 11 + -7x + 7x + x2 + -1x2

Combine like terms: -11 + 11 = 0
18 + 7x + -1x2 = 0 + -7x + 7x + x2 + -1x2
18 + 7x + -1x2 = -7x + 7x + x2 + -1x2

Combine like terms: -7x + 7x = 0
18 + 7x + -1x2 = 0 + x2 + -1x2
18 + 7x + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
18 + 7x + -1x2 = 0

Factor a trinomial.
(9 + -1x)(2 + x) = 0

Subproblem 1

Set the factor '(9 + -1x)' equal to zero and attempt to solve: Simplifying 9 + -1x = 0 Solving 9 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = 0 + -9 -1x = 0 + -9 Combine like terms: 0 + -9 = -9 -1x = -9 Divide each side by '-1'. x = 9 Simplifying x = 9

Subproblem 2

Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2

Solution

x = {9, -2}

See similar equations:

| 4x^2-16x=-y^2+10y-40 | | 9x+4x+3+8=4x+3x+8x | | lnx=-1/5 | | 5y-4=13y+68 | | 4x+22=3+7x-8 | | 1/3(x-4)^=1 | | (2000(1-x/60)^2)/x | | 6+1-2x=5x+x-7 | | (5x+20)(3x+66)= | | 6x+7z=4+5y | | Ydy/dx-e^x=O | | 7(2x-9)=43 | | (2s-3)+s+(3s-30)=207 | | r+21=15 | | 5x-3=12+x-1+2 | | 40+2*5= | | k^4-100k=0 | | 3/2x-1/3x | | 0=-16t^2+4.5t | | 16c^2-70c+49=0 | | 1/2=d/4 | | 8-x=3x+8 | | 3x+1x=36 | | y/50=-21 | | 2x^4-13x^2+17=0 | | p/2.3=4 | | a+b=19 | | x/5.3=0.7 | | 80=-8k | | -5=1.5(6x-2)+7x | | 4(4x+2)=21x+6-5x+2 | | x/2=4=13 |

Equations solver categories